Integrated Full-Length Transcriptome and Metabolome Profiling Reveals Flavonoid Regulation in Response to Freezing Stress in Potato - Zhu, Z.; Wei, L.; Guo, L.; Bao, H.; Wang, X.; Kear, P.; Wang, Z.; Zhu, G. (MDPI, 2023)
Cold stress impairs plant growth and development, resulting in crop failure. Cultivated potato (Solanum tuberosum L.) is sensitive to freezing, while its wild relative, S. commersonii, has a strong freezing tolerance. To decipher the anti-freezing mechanism of CM, we carried out a transcriptomic and metabolomic analysis of an anti-freezing variety of CM (a type of S. commersonii) and a freeze-sensitive variety of DM (a type of Solanum tuberosum L.). A total of 49,232 high-quality transcripts from 12,811 gene loci, including 46,772 coding sequences and 2018 non-coding RNAs, were identified. KEEG enrichment analysis of differentially expressed genes (DEGs) between the two varieties showed that the flavonoid biosynthesis pathway was strongly induced by freezing stress, which was proven by flavonoid metabolome analysis. Consistent with the accumulation of more flavonoids, nearly all the pathway genes were significantly upregulated in CM than those in DM. The transcript levels of two chalcone synthase (CHS-1) isoforms and four isoforms of flavonoid 3′-hydroxylase (F3′H-1) were confirmed by qRT-PCR. Co-expression analysis identified one Myb-related and three UGTs (UDP-glycosyltransferase) that were significantly upregulated in CM during freezing stress. Our findings support that the flavonoid pathway was significantly enhanced by freezing stress and the greater accumulation ofglycosylatedflavonoids in resistant types than that of sensitive types, maybe accounting for the increased freezing tolerance of freeze-resistant potato varieties.